Fuel oil characteristics and applications: economic and technological aspects. (3rd May 2019) - Man, Z.; Ebadi, A. G.; Mostafavi, S. M.; Surendar, A.
Abstract: This review explains some of the most important properties of heavy oils compared to other fuels. Although there is numerous heavy oil upgrading methods, this study was focused on the production of synthesis gas. Alongside advantages, some of the limitations of using heavy oil are also explained, including high heavy oil upgrading costs. In this regard, some of the most important heavy oil upgrading methods were selected and their economic characteristics were compared.